Management of internal root resorption in the maxillary central incisor with fractured root using Biodentine. Issue 7 (21st July 2021) - Sanaei‐rad, Parisa; Bolbolian, Marjan; Nouri, Faranak; Momeni, Ehsan
Abstract: Biodentine is desirable to successfully manage internal root resorption, and the MTA apical plug backfilled with thermoplasticized gutta‐percha is suggested for the tooth with external apical root resorption. Abstract : Biodentine is desirable to successfully manage internal root resorption, and the MTA apical plug backfilled with thermoplasticized gutta‐percha is suggested for the tooth with external apical root resorption.